2020
DOI: 10.1007/s13538-020-00790-7
|View full text |Cite
|
Sign up to set email alerts
|

The Spontaneous Exchange Bias Effect on La1.5Ba0.5CoMnO6

Abstract: La 1.5 Ba 0.5 CoMnO 6 is a re-entrant cluster glass material exhibiting a robust negative exchange bias (EB) effect even after being cooled from an unmagnetized state down to low temperature in zero magnetic field. Here we thoroughly investigate this phenomena by performing magnetization as a function of applied field [M(H )] measurements at several different temperatures and maximum applied magnetic fields (H m ). The spontaneous EB (SEB) effect is observed below 20 K, and shows a maximum value for H m = 75 k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The XRD patterns revealed that all samples belong to the rhombohedral R 3c space group, as expected since both x = 0 and 0.5 end members present the same crystal symmetry 9,10 . Fig.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The XRD patterns revealed that all samples belong to the rhombohedral R 3c space group, as expected since both x = 0 and 0.5 end members present the same crystal symmetry 9,10 . Fig.…”
supporting
confidence: 76%
“…S2 in SM). Previous reports of magnetization, muon spin rotation and relaxation, XAS and XMCD measurements for the x = 0 and 0.5 compounds have shown a mixed valence state for Co (Co 2+ /Co 3+ ), while for Mn it was found a nearly tetravalent state, although some small amount of Mn 3+ was detected 9,10,12 . In these studies the first transition temperature, T C1 , was ascribed to the Co 2+ -O-Mn 4+ FM coupling, the second one, T C2 , to the Co 3+ -O-Mn 3+ FM coupling, while the third anomaly observed at lower T is most likely related to the Co 3+ -O-Mn 4+ AFM coupling.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The refinement indicates that x = 0.25 compound crystallizes with two crystallographic phases, with ∼ 20% of its mass weight in the orthorhombic P nma space group and ∼ 80% in the rhombohedral R 3c one. This is reasonable, since x = 0 parent compound forms in P nma space group [15] while the x = 0.5 sample belongs to R 3c [18]. As the Ba-concentration increases, a tendency toward hexagonal symmetry is observed, with x = 0.75 and 1.0 samples forming with ∼ 5% and ∼ 30% of P 6 3 /mmc space group, respectively.…”
Section: Resultsmentioning
confidence: 67%
“…In that case, the Ca-based sample exhibits a small UA while for the Ba-based one, the magnitude of the effect is intermediate between those of Ca-and Sr-based compounds. Such pronounced changes in the SEB effect from one sample to another can be attributed to different proportions of Co 2+ /Co 3+ and to the spin state of Co 3+ , that affect the uncompensated antiferromagnetic (AFM) Co-Mn coupling [17,18,19]. Interestingly, single-crystalline La 2−x A x CoMnO 6 (A = Ca, Sr) samples are not reentrant SG and showed no trace of SEB effect, giving further evidence that an SG-like phase is necessary for the emergence of SEB [20] Very recently, a thorough investigation of the La 1.5 (Sr 0.5−x Ba x )CoMnO 6 series has evidenced how the crystal structure affects the SEB effect by indirectly altering the systems' electronic structure [21].…”
Section: Introductionmentioning
confidence: 99%